(untitled) (Journal of Asian Development Studies, 2025)
This study examines the impact of AI-powered personalisation on purchase intentions, with trust as a mediating factor. It explores how AI-driven recommendations influence consumer decision-making and whether trust enhances this effect. Using a quantitative research design, data were collected from 400 randomly selected respondents. Regression analysis was applied to test the direct and mediating effects of AI personalisation on purchase intentions. The results indicate that AI-powered personalisation significantly enhances purchase intentions, and trust mediates this relationship. Consumers are more likely to act on personalised recommendations when they perceive AI systems as reliable and beneficial. Businesses should leverage AI-driven personalisation strategies while simultaneously fostering consumer trust to maximise purchasing behaviour. Ensuring transparency and reliability in AI recommendations can enhance consumer acceptance and engagement. This study contributes to the growing body of research on AI in consumer behaviour by highlighting the role of trust in AI-powered personalisation. It offers valuable insights for businesses and marketers looking to optimise AI-driven customer experiences.